Open borders in East Africa - Monsportová, Tereza (2018)
The aim of this bachelor thesis is to find out the main aspects of open borders policy in East Africa. What are the main causes and which consequences the states are then struggling with. The reason for this topic is primarily the topicality because migratory and refugee politics are being discussed almost all over the world. States have often different approaches to this. In my thesis I will deal with open borders and case study will help me with my research. Thanks to case study I will be able to find out the main causes and consequences of migration and refugee crisis first in East Africa and then in Ethiopia. Ethiopia is important as a destination country and as a country of origin. We can find several reasons for open borders in this region from higher humanitarian aid to remittances. Important is also the possibility of generalizing the implications in different part of the world because if we manage the migration properly we can gain a lot of positive effects.